Development and validation of an overuse injury questionnaire for youth athletes: The Youth Overuse Injury Questionnaire - Lau, R.; Mukherjee, S. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Current overuse injury registration methods may underestimate the prevalence and severity of overuse injuries for youth athletes. This study developed and validated a new injury registration method for youth athletes based on the improved Oslo Sports Trauma Research Centre Overuse Injury Questionnaire (OSTRC-O2), termed as the Youth Overuse Injury Questionnaire (YOvIQ).